Desarrollo de una aplicación web para regulación de presupuestos en proyectos eléctricos aplicando la herramienta Django en la empresa INGELEC-BM - Escobar Chávez, Osmar Patricio (2022)
Over time, technology allows to automate tasks and even improve them with new agile and intuitive applications, maintaining a structured design in order to meet the needs of customers, optimize resources and in the shortest possible time. INGELEC-BM, a company dedicated to the design and construction of electrical projects, needed tools to help manage the data it processes, it was losing a lot of time, resources and money because the administrative activities related to the budget were not automated, to contribute to the growth of the company requires a viable tool that fits the needs of the company. Therefore, a web application was created that in addition to mitigating the shortcomings of the information management process, it also helps optimize the performance of resources in the activities and also has an impact on productivity. In the development of the present software, open source access technology platforms were used, in addition to the application of programming languages such as PYTHON and methodologies such as Kanban, its simple application in databases such as PostgreSQL was also demonstrated. The estimated times of the evaluated systems were obtained for the non-automated system through a survey to the manager of the company where he collected the times of the processes and for the times of the web application was used one of the three metrics of Kanban called Cycle Time, with the help of the Kanbanize tool it was possible to obtain data from the same processes previously evaluated and through a comparison of the two results were achieved visible results, in which each data process in the modules had a substantial improvement